Analysis of a phenylalanine ammonia-lyase gene sequence from Arachis hypogaea l. and its transcript abundance in induced systemic resistance against Sclerotium rolfsii - Tonelli, Maria Laura (2013)
Phenylalanine ammonia-lyase (PAL) is an important plant enzyme in pathogen defense. The purpose of this work was to analyze the phylogenetic relationships of a partial PAL gene sequence from Arachis hypogaea L. (peanut) cv. Tegua (designated AhPAL), a PAL sequence from cultivar JL24 and PAL sequences from other legumes and non-legumes plants. In addition, changes in the AhPAL transcript abundance related to induced systemic resistance (ISR) were also evaluated. AhPAL sequence shows high level of similarity with PAL genes and proteins from several plant species, including legumes and non-legumes. Quantification of relative transcript abundance indicated that AhPAL could be involved in the A. hypogaea cv. Tegua response towards the phytopathogen Sclerotium rolfsii.